AB0349 Denosumab versus Bisphosphonates for Treatment of Rheumatoid Arthritis. (15th July 2016) - Kinoshita, H.; Miyakoshi, N.; Miyamoto, S.; Abe, S.; Sugimura, Y.; Shimada, Y.; ,
Abstract : Background: Rheumatoid arthritis (RA), caused by upregulation of proinflammatory cytokines, is characterized by overexpression of receptor activator of nuclear factor kappa-B ligand (RANKL) in the synovial membrane, which promotes osteoclast differentiation and thus increases bone resorption. Denosumab, an antibody against RANKL, prevents RANKL/RANK interactions and inhibits osteoclast-mediated bone resorption. This study investigated whether denosumab can prevent the inflammation caused by excessive bone resorption in RA patients in comparison with bisphosphonates, which directly prevent osteoclast-mediated bone resorption. Objectives: RA patients in the Akita Orthopedic Group on Rheumatoid Arthritis (AORA) registry included 58 and 49 newly denosumab-treated and bisphosphonate-treated patients, respectively. Methods: For RA, the Steinbrocker classification was measured at pretreatment and use of glucocorticoid, methotrexate, and biological agents, DAS28-ESR, simplified disease activity index (SDAI), erythrocyte sedimentation rate, and matrix metalloproteinase 3 were measured at pre-treatment and 6 and 12 months post-treatment. For bone metabolism, bone-specific alkaline phosphatase (BAP), indicating bone formation, tartrate-resistant acid phosphatase 5b (TRACP-5b), indicating bone resorption, and bone mineral density (BMD) of the lumbar and femoral neck were measured at pre-treatment, and 6 and 12 months post-treatment. Results: For RA, the Steinbrocker class and stage were significantly higher in the denosumab group compared with the bisphosphonate group (p<0.0001 and p=0.0004, respectively). Use of biological agents was also significantly higher in the denosumab group compared with the bisphosphonate group at pre-treatment and 12 months post-treatment (p=0.006 and p=0.0467, respectively). There were no significant differences in DAS28-ESR and SDAI between the periods for denosumab or bisphosphonates (Figure ). For bone metabolism, denosumab reduced BAP at 6 and 12 months post-treatment compared with pre-treatment (p=0.006 and p=0.0132, respectively) (Figure). There were no significant differences in BMD of the lumbar and femoral neck between the periods for denosumab or bisphosphonates, but denosumab revealed a tendency toward increases and bisphosphonates revealed a tendency toward decreases. Conclusions: Denosumab and bisphosphonates did not suppress RA activity, but denosumab prevented excessive bone turnover more effectively than bisphosphonates. References: Cohen SB, Dore RK, Lane NE, et al. Denosumab treatment effects on structural damage, bone mineral density, and bone turnover in rheumatoid arthritis: a twelve-month, multicenter, randomized, double-blind, placebo-controlled, phase II clinical trial. Arthritis Rheum 58 (5): 1299–1309, 2008. Acknowledgement: We thank all the patients and AORA members who participated in this research. Disclosure of Interest: None declared